2021
DOI: 10.3390/nano11092334
|View full text |Cite|
|
Sign up to set email alerts
|

Hyaluronic Acid/Collagen Nanofiber Tubular Scaffolds Support Endothelial Cell Proliferation, Phenotypic Shape and Endothelialization

Abstract: In this study, we designed and synthetized artificial vascular scaffolds based on nanofibers of collagen functionalized with hyaluronic acid (HA) in order to direct the phenotypic shape, proliferation, and complete endothelization of mouse primary aortic endothelial cells (PAECs). Layered tubular HA/collagen nanofibers were prepared using electrospinning and crosslinking process. The obtained scaffold is composed of a thin inner layer and a thick outer layer that structurally mimic the layer the intima and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
(71 reference statements)
1
20
0
Order By: Relevance
“…In vitro cell experiments confirmed that HA nanofibers on the inner surface of scaffolds can promote the adhesion of vascular ECs, while the porosity of scaffolds can promote the histomorphogenesis of vascular smooth muscle by promoting their infiltration and diffusion from outer wall surface. These results are consistent with previous reports highlighting that cell scaffold biophysical properties such as stiffness, structure and topography are critical for normal cell function [ 12 , 13 , 26 , 37 , 38 ]. Furthermore, the composite scaffold can provide a complete 3D nanofibrous matrix microenvironment for the proliferation of vascular EC and SMC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In vitro cell experiments confirmed that HA nanofibers on the inner surface of scaffolds can promote the adhesion of vascular ECs, while the porosity of scaffolds can promote the histomorphogenesis of vascular smooth muscle by promoting their infiltration and diffusion from outer wall surface. These results are consistent with previous reports highlighting that cell scaffold biophysical properties such as stiffness, structure and topography are critical for normal cell function [ 12 , 13 , 26 , 37 , 38 ]. Furthermore, the composite scaffold can provide a complete 3D nanofibrous matrix microenvironment for the proliferation of vascular EC and SMC.…”
Section: Discussionsupporting
confidence: 93%
“…The ultimate goal of tissue-engineered vascular scaffolds is to promote vascular reconstruction and functional recovery of damaged vessels. The effect of reconstruction is closely related to the biophysical and biochemical signals from scaffolds [ 20 , 36 38 ]. In this study, collagen and HA were used as raw materials and a porous, hierarchical composite tubular vascular nanofibrous scaffold was successfully prepared by using the electrospinning technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of tissue engineering, the products derived from HA have shown a high biocompatibility, a reduced immunogenicity and a high biodegradability. HA-based scaffolds can be also synthesized in different forms including hydrogels, nets, fibers and porous sponges [40,41]. Interestingly, in order to limit the use of acrylamide, innovative chemical-pharmaceutical technologies have made it possible to synthesize derivatives in which the cross-linking HA is determined by residues of the safer cinnamic acid (cross-linked HA).…”
Section: Discussionmentioning
confidence: 99%
“…As a method to recapitulate the fibrous nature of native ECM, electrospinning has emerged as a simple, cost-effective, and versatile material-processing technique that is used to fabricate continuous, ultrafine fibers from the micro- to nanoscale. Via control of the electrospinning parameters ( e.g. , voltage, flow rate, and working distance), one can straightforwardly control the morphologies, diameters, and pore sizes of nanofibers. , The large specific surface area, high porosity, and spatial interconnectivity of electrospun nanofibers favor endothelial cell adhesion, proliferation, migration, and angiogenesis. Niu and Galluzzi fabricated a tubular nanofibrous scaffold based on collagen and hyaluronic acid, which was reported to support endothelial cell proliferation, phenotypic shape, and endothelialization . Moreover, electrospun scaffolds can be further functionalized by incorporation of or conjugation with angiogenic components ( e.g.…”
Section: Introductionmentioning
confidence: 99%